2013
DOI: 10.1007/s00253-013-5434-4
|View full text |Cite
|
Sign up to set email alerts
|

Phagomagnetic immunoassay for the rapid detection of Salmonella

Abstract: This work explores the use of the phage P22 in a phagomagnetic immunoassay for the rapid detection of Salmonella. The covalent attachment of wild-type phages was performed on two different magnetic carriers: carboxyl-activated magnetic nanoparticles (300 nm) and tosyl-activated magnetic microparticles (2.8 μm). The bacteria were captured and preconcentrated by the phage-modified magnetic particles, followed by the detection using specific anti-Salmonella antibodies conjugated to horseradish peroxidase as an op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…Interestingly, by combining phage P22-based magnetic separation with anti-Salmonella antibodies, Laube et al reported a detection limit of 19 CFU · ml Ϫ1 Salmonella, representing one of the most sensitive phage-based detection assays to date (34). However, it was also noted that the phage P22 particles used caused cell lysis (34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, by combining phage P22-based magnetic separation with anti-Salmonella antibodies, Laube et al reported a detection limit of 19 CFU · ml Ϫ1 Salmonella, representing one of the most sensitive phage-based detection assays to date (34). However, it was also noted that the phage P22 particles used caused cell lysis (34).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, by combining phage P22-based magnetic separation with anti-Salmonella antibodies, Laube et al reported a detection limit of 19 CFU · ml Ϫ1 Salmonella, representing one of the most sensitive phage-based detection assays to date (34). However, it was also noted that the phage P22 particles used caused cell lysis (34). While phage-induced lysis can be combined with IMS to detect E. coli (62) and Salmonella (63) based on phage-encoded biomarker amplification, lysis may also be problematic if downstream identification requires the recovery of viable cells-an issue not associated with LTFs and other phage-encoded proteins with no inherent lytic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar sensitivity decreases in testing food samples have been observed in other studies. Laube et al used phagoomagnetic immunoassay to detect S. Typhimurium in LB broth and milk, and obtained detection limits of 10 and 19 CFU/mL without any pre-enrichment step, respectively, which indicates the sensitivity of the assay decreased by nearly twofold in food testing (Laube et al, 2014). Similarly, Amaro et al detected S. Typhimurium in various food samples, including chicken broth, low fat milk and freshly squeezed orange juice, using scano-magneto immunoassay based on a nano-composite (Amaro et al, 2012).…”
Section: Detection Of Salmonella In Food Samplesmentioning
confidence: 97%
“…Bacteriophages have also been explored as a means to capture Salmonella cells. Phages may ofer some advantages over antibodies given their inherent speciicity for host cells, their ease of production in bacteria versus animals or eukaryotic cell culture, and their relative stability in harsh conditions such as pH and temperature extremes [70].…”
Section: Aptamer-based Detection Assaymentioning
confidence: 99%